Unmasking Wildlife Crime: The Critical Role of Forensic Science in Legal Enforcement - Dr. Neha Mishra; Dr. Atul Jain; Dr. Papiya Golder; Dr. Pranshul Pathak (The Bioscan, 2025)
crime, including illegal poaching, trafficking, and the trade in endangered species, has escalated into one of the most pressing global threats to biodiversity and ecosystem integrity. These illicit activities have profound and far-reaching consequences, contributing to the depletion of critical species, destabilization of ecosystems, and disruption of ecological balance. The complexity and transnational nature of wildlife crime, coupled with the involvement of organized criminal networks, have increasingly challenged traditional law enforcement mechanisms, rendering them insufficient in addressing the scale of the issue. Consequently, the application of forensic science in wildlife crime investigations has emerged as a vital tool for providing irrefutable scientific evidence to support the prosecution of offenders. Wildlife forensics, a specialized discipline that combines zoological research with forensic science, is pivotal in bridging the gap between criminal justice and biodiversity conservation. This paper critically examines the role of wildlife forensics in the investigation, identification, and prosecution of wildlife crimes, with a particular focus on advanced forensic techniques such as DNA analysis, stable isotope analysis, and morphometric identification. These methods not only enable the precise identification of species involved in illegal trade but also facilitate the tracing of wildlife products to their geographical origins, thereby establishing strong links between criminals and illicit activities. Through a detailed exploration of relevant case studies, legal frameworks, and forensic methodologies, this study demonstrates how wildlife forensics has been successfully employed to secure convictions and dismantle transnational criminal syndicates engaged in poaching and trafficking. The analysis highlights the growing significance of interdisciplinary collaboration between forensic scientists, legal professionals, and policymakers, which is crucial for the effective enforcement of wildlife protection laws. Furthermore, the paper underscores the transformative potential of wildlife forensics in enhancing global wildlife law enforcement efforts, ensuring justice for endangered species, and strengthening legal accountability for wildlife crimes.